Understanding the Perception of Adolescent Challenges in Body Mass Index Reduction: A Qualitative Study - Suwarsi; Joshepine Lorica; Hastuti, Agustina Sri Oktri (Journal of Advanced Health Informatics Research, 2023)
A weight loss program for adolescents needs to be done immediately, considering that the number of adolescents who are obese is increasing. This research contributes to identifying the challenges faced by overweight adolescents in weight loss programs. Data was collected by filling out a questionnaire given directly to the participants. The location where the research was conducted at Yogyakarta City, Indonesia. The questionnaire has been tested for validity and reliability with a value of more than 0.85. This study uses a qualitative research design, with a sample of adolescents aged 15-19 years who are obese. The number of participants is 15; according to the inclusion criteria, the data is taken through in-depth interviews. Results: The difficulty of overweight adolescents in losing weight is due to the lack of parental support in serving food and the lack of support from friends in diet programs. Health programs for adolescents, especially weight loss programs, need to involve peers and support from parents